2020
DOI: 10.1186/s13104-020-05334-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of drug resistant polymorphisms in Plasmodium falciparum isolates from Southwest, Nigeria

Abstract: Objective Nigeria bears 25% of global malaria burden despite concerted efforts towards its control and elimination. The emergence of drug resistance to first line drugs, artemisinin combination therapies (ACTs), indicates an urgent need for continuous molecular surveillance of drug resistance especially in high burden countries where drug interventions are heavily relied on. This study describes mutations in Plasmodium falciparum genes associated with drug resistance in malaria; Pfk13, Pfmdr1, PfATPase6 and Pf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…In this study, the prevalence of the Pfcrt mutation reduced from 72.2% in 2012 to 22.6% in 2019, and decreased steadily, and significantly year-by-year (Figure 1A). The study of Tola et al reported that the prevalence of mutant Pfcrt (CVIET) was 45% in 2014 in southwestern Nigeria (Tola et al, 2020), and Lu et al reported that the prevalence of Pfcrt 76T was 46.9% in Nigeria during 2011-2014 (Lu et al, 2017), and the prevalence of mutant Pfcrt was 41.9% in Nigeria during 2012-2015 in our published study (Zhou et al, 2016), the results of the three studies performed in Nigeria were similar. However, there are few recent data on the prevalence in Nigeria.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, the prevalence of the Pfcrt mutation reduced from 72.2% in 2012 to 22.6% in 2019, and decreased steadily, and significantly year-by-year (Figure 1A). The study of Tola et al reported that the prevalence of mutant Pfcrt (CVIET) was 45% in 2014 in southwestern Nigeria (Tola et al, 2020), and Lu et al reported that the prevalence of Pfcrt 76T was 46.9% in Nigeria during 2011-2014 (Lu et al, 2017), and the prevalence of mutant Pfcrt was 41.9% in Nigeria during 2012-2015 in our published study (Zhou et al, 2016), the results of the three studies performed in Nigeria were similar. However, there are few recent data on the prevalence in Nigeria.…”
Section: Discussionsupporting
confidence: 70%
“…Several mutations of PfK13 have also been described in Nigerian isolates, including one non-synonymous mutation G665C discovered in southwestern Nigeria (Oboh et al, 2018), and six mutations (E433G, F434I, F434S, I684N, I684T, and E688K) identified in northern Nigeria, among which E433G and E688K were identified from isolates with the delayed clearance (Abubakar et al, 2020). The study performed in southwestern Nigeria in 2014 identified eight nonsynonymous mutations in PfK13, including G496S, R539F, I543V, V566K, D584I, C580Y, and a deletion variant A557; the C580Y mutant was suspected by allelic discrimination in two samples with mixed genotypes (Tola et al, 2020). In this study, two non-synonymous mutations, S693F and Q613H, were identified in two isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria is also one of 11 countries which have reported Pfhrp2/3 deletions that compromise the utility of HPR2-based diagnostic tests for the detection of malaria cases [ 4 ]. Although the levels of P. falciparum resistance to sulfadoxine-pyrimethamine have remained low from 2000 to 2020 in western Africa including Nigeria, the rising incidence of drug resistance polymorphisms to first line drugs (artemisinin combination therapy) is a major challenge to control malaria [ 73 , 74 ]…”
Section: Epidemiological Data From Countries Of Origin For Importementioning
confidence: 99%
“…One study showed that the levels of P. falciparum resistance to sulfadoxine/pyrimethamine have remained low from 2000 to 2020 in western Africa, including in Nigeria [ 91 ]. However, the rising incidence of polymorphisms in P. falciparum genes (Pfk13, Pfmdr1, PfATPase6 and Pfcrt) associated with drug resistance to first-line drugs (artemisinin combination therapy) is a major challenge in malaria control efforts [ 92 ]. Previous studies from GCC countries have shown that travelers or returning travelers from Nigeria have presented with imported malaria cases in Kuwait, Qatar, Saudi Arabia and UAE [ 36 , 44 , 45 , 46 , 47 , 49 , 51 ].…”
Section: Malaria Status Among Countries Contributing Most Of the Imported Malaria Cases In Gcc Countriesmentioning
confidence: 99%